Keunggulan Bersaing Pada Usaha Rumah Makan Padang di Pekanbaru Berbasiskan Kearifan Lokal - Annisa Mardatillah; Rosmayani Rosmayani (Universitas Riau, 2023)
This study aims to analyze the effect of knowledge management on sustainable competitive advantage through local wisdom in a Padang restaurant business in Pekanbaru. Knowledge-sharing activities in the Padang restaurant business in Pekanbaru are an essential problem to study because this still needs to be optimally implemented. The low understanding of business actors in carrying out knowledge-sharing activities is challenging to achieve competitive competitiveness. Even though the same cultural background can be a potential strength in this knowledge-sharing activity. The sample for this research was employees of a Padang restaurant business in Pekanbaru, which was determined by purposive sampling. The analysis technique uses SEM PLS, with the study results showing that knowledge management influences sustainable competitive advantage through local wisdom in the Padang restaurant business in Pekanbaru. This research contributes empirically to an essential understanding of knowledge management based on local learning to achieve sustainable competitive advantage in Padang restaurant businesses in Pekanbaru and successfully tests local wisdom as a moderating variable.